Chronic Alcohol Exposure Induced Neuroapoptosis: Diminishing Effect of Ethyl Acetate Fraction from Aralia elata. (9th May 2019) - Kwon, Bong Seok; Kim, Jong Min; Park, Seon Kyeong; Kang, Jin Yong; Kang, Jeong Eun; Lee, Chang Jun; Park, Sang Hyun; Park, Su Bin; Yoo, Seul Ki; Lee, Uk; Kim, Dae-Ok; Heo, Ho Jin
Abstract : An ethyl acetate fraction from Aralia elata (AEEF) was investigated to confirm its neuronal cell protective effect on ethanol-induced cytotoxicity in MC-IXC cells and its ameliorating effect on neurodegeneration in chronic alcohol-induced mice. The neuroprotective effect was examined by methylthiazolyldiphenyl-tetrazolium bromide (MTT) and 2 ′, 7 ′ -dichlorodihydrofluorescein diacetate (DCF-DA) assays. As a result, AEEF reduced alcohol-induced cytotoxicity and oxidative stress. To evaluate the improvement of learning, memory ability, and spatial cognition, Y-maze, passive avoidance, and Morris water maze tests were conducted. The AEEF groups showed an alleviation of the decrease in cognitive function in alcohol-treated mice. Then, malondialdehyde (MDA) levels and the superoxide dismutase (SOD) content were measured to evaluate the antioxidant effect of AEEF in the brain tissue. Treatment with AEEF showed a considerable ameliorating effect on biomarkers such as SOD and MDA content in alcohol-induced mice. To assess the cerebral cholinergic system involved in neuronal signaling, acetylcholinesterase (AChE) activity and acetylcholine (ACh) content were measured. The AEEF groups showed increased ACh levels and decreased AChE activities. In addition, AEEF prevented alcohol-induced neuronal apoptosis via improvement of mitochondrial activity, including reactive oxygen species levels, mitochondrial membrane potential, and adenosine triphosphate content. AEEF inhibited apoptotic signals by regulating phosphorylated c-Jun N-terminal kinases ( p -JNK), phosphorylated protein kinase B ( p -Akt), Bcl-2-associated X protein (BAX), and phosphorylated Tau ( p -Tau). Finally, the bioactive compounds of AEEF were identified as caffeoylquinic acid (CQA), 3, 5-dicaffeoylquinic acid (3, 5-diCQA), and chikusetsusaponin IVa using the UPLC-Q-TOF-MS system.